2018
DOI: 10.1093/aobpla/ply063
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying temporal change in plant population attributes: insights from a resurrection approach

Abstract: Rapid evolution in annual plants can be quantified by comparing phenotypic and genetic changes between past and contemporary individuals from the same populations over several generations. Such knowledge will help understand the response of plants to rapid environmental shifts, such as the ones imposed by global climate change. To that end, we undertook a resurrection approach in Spanish populations of the annual plant Arabidopsis thaliana that were sampled twice over a decade. Annual weather records were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 101 publications
(150 reference statements)
1
27
1
Order By: Relevance
“…However, we need to deal with the latter to understand the former. In this sense, recent resurrection studies showed that natural A. thaliana populations exhibited substantial changes in their genetic composition in just a decade [77,78]. The extent of temporal genetic variation in A. thaliana represents a reminder that populations are not static, and that the geographic distribution of genetic diversity within and among-populations is changing too.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we need to deal with the latter to understand the former. In this sense, recent resurrection studies showed that natural A. thaliana populations exhibited substantial changes in their genetic composition in just a decade [77,78]. The extent of temporal genetic variation in A. thaliana represents a reminder that populations are not static, and that the geographic distribution of genetic diversity within and among-populations is changing too.…”
Section: Discussionmentioning
confidence: 99%
“…Natural A. thaliana populations are made of patches of individuals widely differing in size and density, which is important when it comes to design a sampling scheme to study the spatio-temporal distribution of genetic diversity in A. thaliana [49,57,65,77]. For each population and whenever possible, we collected seeds from several individuals from different patches (separated 1-20 m from each other) representing well each study population.…”
Section: Source Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid evolution in response to conditions linked to climate change has been detected for numerous taxa in as few as a couple of generations (reviewed in Parmesan, 2006; Franks, Hamann, & Weis, 2018). One approach used to detect this rapid evolution in plants is the resurrection study, in which seeds collected at one point in time (ancestral) are grown and compared with those collected later (descendant; Etterson et al, 2016; Franks, 2011; Franks et al, 2018; Franks, Sim, & Weis, 2007; Gómez, Méndez‐Vigo, Marcer, Alonso‐Blanco, & Picó, 2018; Hamann et al, 2018; Sultan, Horgan‐Kobelski, Nichols, Riggs, & Waples, 2012; Thomann, Imbert, Engstrand, & Cheptou, 2015; Vigouroux et al, 2011). For plants, this approach is dependent on the collection and storage of seeds over a period in which an environmental change occurs.…”
Section: Introductionmentioning
confidence: 99%